2011
DOI: 10.1007/s10067-011-1876-1
|View full text |Cite
|
Sign up to set email alerts
|

Association of clinical and genetical features in FMF with focus on MEFV strip assay sensitivity in 452 children from western Anatolia, Turkey

Abstract: The aim of this study was to determine the relationship between clinical findings and the most common mutated alleles of MEFV gene in a childhood population and to determine the sensitivity of the 12-mutation-strip assay test in familial Mediterranean fever (FMF). Records of 452 FMF children living in western Anatolia, Turkey, (12.3 ± 4.7 years mean) were retrospectively reviewed. Of the 408 patients who met the Tel-Hashomer criteria, 364 were classified into two main groups (two-mutant/one-mutant allele) eith… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
49
1
8

Year Published

2013
2013
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(64 citation statements)
references
References 41 publications
6
49
1
8
Order By: Relevance
“…[11][12][13][14][15][16] In our study group, the most frequent MEFV mutation was also M694V, and based on this result, we suggested that the distribution of MEFV gene mutations does not differ greatly between the different geographic areas of Turkey.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…[11][12][13][14][15][16] In our study group, the most frequent MEFV mutation was also M694V, and based on this result, we suggested that the distribution of MEFV gene mutations does not differ greatly between the different geographic areas of Turkey.…”
Section: Discussionmentioning
confidence: 67%
“…Öztürk et al 16 analyzed 452 pediatric FMF patients with a mean age of 12.4±4.7 (range, 2-30 years) and indicated that the common clinical findings were abdominal pain (86.3%), fever (81.9%), myalgia (58.8%) and arthritis/ arthralgia (49%). Six (2.9%) and nine (4.3%) of 207 patients carrying two mutant alleles had amyloidosis and proteinuria respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, genetic testing in the diagnosis of FMF is important in terms of preventing injury caused by amiloid-A (AA) amyloidosis, which is the most severe complication of the disease. Previous studies have shown that the risk of developing severe disease phenotype is higher in patients who are homozygous for M694V (10). It was observed that the homozygous state for M694V was a high risk factor for amiloidosis in Armenians, Israelis, and Arabs (11).…”
Section: Familial Meditarenean Fevermentioning
confidence: 99%
“…3,5,[9][10][11][12][13][14][15][16]20,21 The most common mutation characterized in Turks is the M694V mutation with the frequency of 30-50%. The E148Q mutation occurs at a frequency ranging from 1.4-11.4% according to some previous studies.…”
Section: Patient Genotypesmentioning
confidence: 99%
“…The E148Q mutation occurs at a frequency ranging from 1.4-11.4% according to some previous studies. 7,15,16,[19][20][21] Although, there were disagreement regarding whether the E148Q mutation even exhibit disease, it has been reported as disease causing mutation in FMF. 20 Two recent studies from eastern and southeast Turkey reported that the E148Q mutation occurs at frequencies of 34.1% and 30.7% in these populations, respectively, which is approximate to the frequency that we identified at 40.1%.…”
Section: Patient Genotypesmentioning
confidence: 99%